Analyzing the Impact of Environmental Law on Sustainable Urban Development - wulan retno sari; Pathus Surur; Bilman permana (Green Social: International Journal of Law and Civil Affairs, 2024)
Environmental laws play a critical role in shaping sustainable urban development by setting guidelines and regulations for managing natural resources, waste, and pollution. This study explores the influence of environmental law on sustainable city planning, examining case studies from various urban areas to assess the efficacy of these laws in promoting green spaces, reducing carbon emissions, and enhancing public health. The research highlights legal challenges and provides recommendations for policymakers aiming to balance urban expansion with environmental preservation.